Moving in the Anthropocene: Global reductions in terrestrial mammalian movements - Tucker, Marlee A.; Boehning-Gaese, Katrin; Fagan, William F.; Fryxell, John M.; Van Moorter, Bram; Alberts, Susan C.; Ali, Abdullahi H.; Allen, Andrew M.; Attias, Nina; Avgar, Tal; Bartlam-Brooks, Hattie; Bayarbaatar, Buuveibaatar; et al. (Amer Assoc Advancement Science, 2018)
Animal movement is fundamental for ecosystem functioning and species survival, yet the effects of the anthropogenic footprint on animal movements have not been estimated across species. Using a unique GPS-tracking database of 803 individuals across 57 species, we found that movements of mammals in areas with a comparatively high human footprint were on average one-half to one-third the extent of their movements in areas with a low human footprint. We attribute this reduction to behavioral changes of individual animals and to the exclusion of species with long-range movements from areas with higher human impact. Global loss of vagility alters a key ecological trait of animals that affects not only population persistence but also ecosystem processes such as predator-prey interactions, nutrient cycling, and disease transmission.